2003
DOI: 10.2337/diacare.26.2.452
|View full text |Cite
|
Sign up to set email alerts
|

Similar Genetic Features and Different Islet Cell Autoantibody Pattern of Latent Autoimmune Diabetes in Adults (LADA) Compared With Adult-Onset Type 1 Diabetes With Rapid Progression

Abstract: OBJECTIVE -To compare the clinical parameters, C-peptide levels, pattern of islet cellspecific autoantibodies, and prevalence of predisposing genotypes in subjects with latent autoimmune diabetes in adults (LADA) and those with adult-onset type 1 diabetes with rapid progression.RESEARCH DESIGN AND METHODS -We evaluated the clinical parameters, Cpeptide levels, and islet cell-specific autoantibodies in 54 LADA, 57 adult-onset type 1 diabetic, and 190 type 2 diabetic patients. Islet cell autoantibodies were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
80
4
13

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 27 publications
(31 reference statements)
10
80
4
13
Order By: Relevance
“…Genetically, young and middle-aged antibody-positive patients were similar with respect to increased prevalence of risk genotypes HLA-DQB1, PTPN22 CT + TT, INS VNTR classI/I and INS VNTR classIIIA/IIIA. These findings are consistent with previous reports [3,41,42]. Although HLA genotyping together with measurements of islet antibodies has been used to identify individuals at risk of type 1 diabetes, until now no genetic markers have been available for type 2 diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Genetically, young and middle-aged antibody-positive patients were similar with respect to increased prevalence of risk genotypes HLA-DQB1, PTPN22 CT + TT, INS VNTR classI/I and INS VNTR classIIIA/IIIA. These findings are consistent with previous reports [3,41,42]. Although HLA genotyping together with measurements of islet antibodies has been used to identify individuals at risk of type 1 diabetes, until now no genetic markers have been available for type 2 diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, it is important to note that DQB1*0602 may not protect subjects from LADA, as one report has shown that these patients have the same frequency of this allele as seen in the general population [27]. Others report no differences in the frequency of highrisk alleles between LADA and older, but more typical type 1 patients [34].…”
Section: Discussionmentioning
confidence: 96%
“…LADA patients may otherwise be clinically indistinguishable from those with type 2 diabetes (diagnosed as adults, can be obese) and can be adequately managed for many years with diet/oral agent therapy [3]. However, the GADA-positive cohort contained fewer individuals with features of the metabolic syndrome, a characteristic more typical of classic type 2 diabetes than LADA [27,28]. It has been proposed that LADA patients with high GADA levels have a more 'type 1 diabetic' phenotype (reduced residual beta cell function, lower BMI and lower frequency of hypertension), and those with low levels a more type 2 diabetes phenotype [29].…”
Section: Discussionmentioning
confidence: 99%